Answer:
(-4, 1)
Explanation:
y = 3/4 x - 4 ---------(1)
y = -x + 3------------------(2)
Substituting y in equation (1)
-x + 3 = 3/4 x - 4
collect like term, that is move the x variables to the left hand -side of the equation and then move the constant to the right hand side of the equation
-x - 3/4 x = -4 - 3
-7x /4 = -7
The negative sign on both the left and right hand side will cancel out each other
7x / 4 = 7
To get the value of x, multiply both-side of the equation by 4/7
7x/4 × 4/ 7 = 7 × 4/7
x = 4
substitute x = 4 into equation (2)
y = -x + 3
y = -4 + 3
y = -1
x = 4 and y = -1
Therefore the solution to the system of the equation is (4, -1)